Hubungan Pengetahuan dan Sikap Ibu Tentang Mp-Asi dengan Pemberian Mp-Asi Pada Bayi 6-24 Bulan di Praktik Bidan Mandiri (PMB) Sri Diana Medan - Sri Widani; Siti Arofah Siregar; Tria Anita; Tharisa Ramadhani; Titik Azizah Nasution; Weni Sri Wahyuni (Universitas Malahayati Lampung, 2025)
ABSTRACT The timing of complementary feeding must be in accordance with the age of the baby. Giving complementary foods too early can have a negative impact on the baby. Infants who receive complementary foods less than 4 months will experience a risk of malnutrition 5 times greater than infants who receive complementary foods at 6 months of age. The purpose of this study was to determine the relationship between maternal knowledge and attitudes about complementary foods with complementary feeding in infants 6-24 months. The type of research used was quantitative using an analytic observational design research design with a cross sectional approach. The population in this study were all mothers who had babies 6-24 months in the Independent Midwife Practice (PMB) Sri Diana Medan which amounted to 65 people. The technique of taking subjects using total sampling of 65 people. The instrument used in this study was a questionnaire to assess knowledge, attitude and complementary feeding. The research data analysis was univariate and bivariate analysis with chi square test. The results explained that there was a relationship between knowledge (p=0.000) and attitude (p=0.001) with complementary feeding. The conclusion of this study is that there is a relationship between knowledge and attitude with complementary feeding in infants 6-24 months. Keywords: Knowledge, Attitude, Complementary Feeding, Infant ABSTRAK Waktu pemberian MP-ASI harus sesuai dengan usia bayi. Pemberian MP-ASI terlalu dini dapat berdampak buruk pada bayi. Bayi yang mendapat MP-ASI kurang dari 4 bulan akan mengalami risiko gizi kurang 5 kali besar disbanding dengan bayo yang mendapatkan MP-ASI pada umur 6 bulan. Tujuan penelitian ini adalah untuk mengetahui Hubungan Pengetahuan Dan Sikap Ibu Tentang MP-ASI Dengan Pemberian MP-ASI Pada Bayi 6-24 Bulan. Jenis penelitian yang digunakan adalah kuantitatif dengan menggunakan desain penelitian desain observasional analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah semua ibu yang memiliki bayi 6-24 bulan di Praktik Bidan Mandiri (PMB) Sri Diana Medan yang berjumlah 65 orang. Teknik pengambilan subjek menggunakan total sampling sebanyak 65 orang. Instrumen yang digunakan dalam penelitian ini adalah kuesioner untuk menilai pengetahuan, sikap dan Pemberian MP-ASI. Analisa data penelitian adalah analisis univariat dan bivariat dengan uji chi square. Hasil penelitian menjelaskan bahwa terdapat hubungan pengetahuan (p=0,000) dan sikap (p=0,001) dengan Pemberian MP-ASI. Kesimpulan penelitian ini adalah terdapat hubungan pengetahuan dan sikap dengan Pemberian MP-ASI pada bayi 6-24 bulan. Kata Kunci: Pengetahuan, Sikap, MP-ASI, Bayi